Determining the Basics of Strengthening Learning: How Students Overcome the Problem of New Testament Interpretation - Siburian, Bernhardt; Limbong, Nurelni (Al Hikmah: Journal of Education, 2023)
This study aims to find the dominant reasons why students experience difficulties in conducting exegesis research in writing a thesis in determining the main points of strengthening learning for the New Testament Interpretation course of the Theological Department, Faculty of Theological Sciences Tarutung State Institute for Christian Studies in 2022. The primary data of this study was obtained from the answers to interview questions for 17 out of 20 student participants who this year are contracting a thesis course. The results of the analysis of the participants' answers showed that the dominant difficulty experienced by the participants was in the preparation of descriptions and analysis of apparatus text, which was at the level of 26%, which was at the level of 0-54% or at the level of difficulty 'unable to do'. Based on the answers of the participants, it was shown that they 'did not understand' in working on the preparation of descriptions and analysis of apparatus text as an answer to the problem of this study. Other reasons equivalent to this level are the difficulty of compiling: analysis of the sentence structure of the text, biblical context/theology (the sacred nature of the text), exegesis works with general patterns, text translation, comparative analysis of text translation, analysis of words, grammars and syntax of the text. The reasons for the difficulty of the second level at 55–64% namely 'not knowing enough or not understanding enough or confused' are in the area: compiling a literary analysis of the text, and establishing a sub-sub-focus of discussion. Based on the results of the data analysis, in addition to other factors, the research team concluded that the participants had limited understanding in working on the detailed instructions presented in the teaching materials of the New Testament Interpretation course. Based on the results of this analysis, recommendations were given: [1] in order to eliminate difficulties in conducting exegesis research in thesis writing, participants must understand and follow technical instructions and examples in working on each analysis of exegesis data on the texts of the New Testament Bible and [2] the teaching lecturers emphasized the two dominant levels of abstraction research difficulties in the learning process of the New Testament Interpretation course.